Chromosome-level reference genome assembly of the gyrfalcon (Falco rusticolus) and population genomics offer insights into the falcon population in Mongolia - Farooq Omar Al-Ajli; Giulio Formenti; Olivier Fedrigo; Alan Tracey; Ying Sims; Kerstin Howe; Ikdam M. Al-Karkhi; Asmaa Ali Althani; Erich D. Jarvis; Sadequr Rahman; Qasim Ayub (Scientific Reports, 2025)
Abstract The taxonomic classification of a falcon population found in the Mongolian Altai region in Asia has been heavily debated for two centuries and previous studies have been inconclusive, hindering a more informed conservation approach. Here, we generated a chromosome-level gyrfalcon reference genome using the Vertebrate Genomes Project (VGP) assembly pipeline. Using whole genome sequences of 49 falcons from different species and populations, including “Altai” falcons, we analyzed their population structure, admixture patterns, and demographic history. We find that the Altai falcons are genomic mosaics of saker and gyrfalcon ancestries, and carry distinct W and mitochondrial haplotypes that cluster with the lanner falcon. The Altai maternally-inherited haplotypes diverged 422,000 years before present (290,000–550,000 YBP) from the ancestor of sakers and gyrfalcons, both of which, in turn, split 109,000 YBP (70,000–150,000 YBP). The Altai W chromosome has 31 coding variants in 29 genes that may possibly influence important structural, behavioral, and reproductive traits. These findings provide insights into the question of Altai falcons as a candidate distinct species.